Density heterogeneity of the Earth’s crust of the Ingul megablock of the Ukrainian Shield according to the data of three-dimensional gravity modeling - Starostenko, V. I.; Kuprienko, P. Ya.; Makarenko, I.B.; Savchenko, A.; Legostaeva, O.V. (Geofizicheskiy Zhurnal, 2015)
According to the data of three-dimensional density modeling at the scale 1:200 000 the peculiarity  of the Earth’s crust structure of the Korsun-Novomirgorod pluton and Novoukrainka massif has been found as well as density distribution by depth and lateral in granitoid massifs of gabbro-anorthosites of the Ingul megablock were given in detail. Density change within the limits of suture and fault zones has been traced, their comparative characteristics has been given.